2006
DOI: 10.1211/jpp.58.5.0015
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibitors from Stephania venosa tuber

Abstract: Acetylcholinesterase (AChE) inhibitors have lately gained interest as potential drugs in the treatment of Alzheimer's disease. Three AChE inhibitors were isolated from tubers of a Thai medicinal plant, Stephania venosa (Bl) Spreng. They were identified as quaternary protoberberine alkaloids, stepharanine, cyclanoline and N-methyl stepholidine. They expressed inhibitory activity on AChE with IC50 values (concentration that caused 50% inhibition of activity) of 14.10 +/- 0.81, 9.23 +/- 3.47 and 31.30 +/- 3.67 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 19 publications
4
54
0
Order By: Relevance
“…Further analysis of HMBC spectrum confirmed the location of methyl group on heteroatom nitrogen which was clearly shown as the protons correlation of position H-8 whiles the N-CH 3 proton was also showed HMBC correlation with C-6 and C-8. This structure was agreement with the related structure, N-methylstepholidine which reported by Ingkaninan et al (2006).…”
Section: O-methylbulbocapnine (3)supporting
confidence: 92%
See 1 more Smart Citation
“…Further analysis of HMBC spectrum confirmed the location of methyl group on heteroatom nitrogen which was clearly shown as the protons correlation of position H-8 whiles the N-CH 3 proton was also showed HMBC correlation with C-6 and C-8. This structure was agreement with the related structure, N-methylstepholidine which reported by Ingkaninan et al (2006).…”
Section: O-methylbulbocapnine (3)supporting
confidence: 92%
“…According to previous research, S. venosa contains several alkaloids, such as protoberberine stephanine cyclanoline and Nmethylstepholidine (Ingkaninan et al, 2006), kamaline (Banerji et al, 1994), (+)-Ncarboxamidostepharine, (-)-O-methylstepharinosine and (-)-stepharinosine (Charles et al, 1987), aporphine (-)-O-acethylsukhodiamine and oxostephanosine (Pharadai et al, 1985). The constituents of S. venosa belonging to showed remarkable cytotoxic activity on human peripheral blood mononuclear cells (Sueblinvong et al, 2007), inhibition the treatment of Alzheimer's disease (Ingkaninan et al, 2006), cytotoxic activity against brine shrimp (Keawpradub et al, 2001) properties. Based on already known preliminary data from bioassay-guided fractionation we promote undertook the studies on cytotoxicity of four crude extracts e.g., hexane, ethyl acetate, acetone and methanol.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of slightly higher AChE inhibitory effects, our present results were consistent with previous reports. 27,35,36) Ingkaninan et al 35) reported that the AChE inhibitory activity of protoberberine alkaloids is associated with planarity, substitutions on the molecule, and the positive charge and aromaticity at the nitrogen. Although several studies have been conducted regarding the AChE inhibitory effects of individual Coptidis Rhizoma alkaloids, 27,[35][36][37] this is the first work on AChE inhibition of groenlandicine.…”
Section: Resultsmentioning
confidence: 99%
“…Both compounds are quaternary BIAs like sanguinarine and berberine. N-methylscoulerine (cyclanoline) can be extracted from several plants of the genus Stephania and has been described as an acetylcholinesterase inhibitor 45 , but to the best of our knowledge N-methylcheilanthifoline has never been detected in plants. The promiscuity of TNMT could also be further explored to generate other quarternary BIAs.…”
Section: Rs)-norlaudanosoline (Nor) (S)-reticuline (Ret) (S)-scoulmentioning
confidence: 99%